Heavy Metal Levels in the Soils of Riyadh City, Saudi Arabia - Al-Shayeb, S.M. (Asian Journal of Chemistry, 2010)
The metals content (Pb, Zn, Co, Cr, Ni and Li) of surface and subsurface soils was determined in Riyadh city. A total of 303 surface soils and 303 corresponding subsurface soil samples were collected at intersection points of a 1 x 1 km grid covering the whole city. Metal levels were investigated in relation to population density, prevailing wind direction, land topography and the structure of the buildings in the city. The levels of Pb, Zn and Cu were found to be elevated in the urban areas (city centre), which are correlated well with the population density. Lead, zinc and to a lesser extent copper distribution in surface soils were affected by the prevailing winds. Lead levels were attributed to the automobile emission whereas Zn and Cu were found to be associated more with the industrial locations than in residential areas. Surface to subsurface ratio results showed Pb, Zn and Cu were largely concentrated in the upper surface soils indicating the atmospheric deposition as the main source of such metals.